“Let’s Just Stop and Take a Breath”: A Community-Driven Approach to Mindfulness Practice in a High Poverty Elementary School (LEARNing Landscapes, 2017)
This case study describes how a high-poverty, linguistically and culturally diverse elementary school came to embed mindfulness in its curriculum and what adults perceived to be the outcomes of the program on students’ well-being. This qualitative case study is based on 25 interviews with teachers, administrators, and community members; classroom observations; and relevant documents. Participants indicated that practicing mindfulness improved student well-being through greater self-awareness and increased ability to articulate their emotions and needs, select strategies to self-regulate, and generalize their practice of mindfulness to out-of-school settings. Implications for practice and research are discussed.
Keywords: mindfulness; self-awareness; well-being; elementary school